Thermophysical characterization of commercial paraffin-based PCMs for low temperature thermal energy storage applications - Matias, T. (2018)
Reliable data on the thermophysical properties of commercial Phase Change Materials (PCMs) is fundamental for the design and modelling of low temperature Thermal Energy Storage (TES) applications. However, data provided by manufacturers is often insufficient and uncertain. In this work, an experimental study was conducted to determine the relevant thermophysical properties of some commercial paraffin-based PCMs, providing a valuable and useful database for ongoing and future studies. Two types of PCMs were evaluated, both microencapsulated and in free-form. Latent heat of fusion, specific heat and melting/solidification temperatures were measured by Modulated Differential Scanning Calorimetry (MDSC). High-resolution modulated thermogravimetric analysis (HiRes-MTGA) was also used to evaluate the thermal stability of the tested PCMs. For the thermal conductivity/diffusivity, the Transient Plane Source (TPS) method (HotDisk) was used. The importance of eliminating phase-transition interferences in the measurements and the effect of the polymer shell in the properties of microencapsulated PCMs were analysed. Properties of both type of PCMs were compared, for the same paraffin composition.